Recognizing and Overcoming Speech Delay in Children: A Case Study of 6-year-old Child in Pematang Cengal - Daulay, Sholihatul Hamidah; Shaumiwaty, Shaumiwaty; Wandini, Rora Rizky; Faridah, Faridah; Suryani, Ira; Pasaribu, Gumarfi Rahis; Hasibuan, Anggi Syariah (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2024)
This article aims to describe how to overcome speech delays in children that can be used and beneficial for parents whose children have speech delays. There are several causes of speech delays experienced by children, namely mental retardation which makes it difficult for children to speak and their brains have difficulty producing language. It is expected that this research would be very useful for parents who have children with speech delays. This study uses a qualitative method with data collection in the form of observations, interviews, and documentation using case studies. The participant in this research was a child aged 6 years in Pematang Cengal with the results of the research to be described. The results obtained in this study are ways to overcome speech delays in children by using several simple ways that can be applied every day such as inviting children to have simple conversations, inviting children to sing and also memorizing lyrics, and reading storybooks to children. The last is by dictating word by word so that the child can repeat it properly and correctly.